Direct Synthesis of Symmetric Diarylethynes from Calcium Carbide and Arylboronic Acids/Esters. Issue 45 (29th November 2017) - Fu, Rugang; Li, Zheng
Abstract : A new methodology for the direct synthesis of symmetric diarylethynes from the reactions of calcium carbide with arylboronic acids/esters is described. Various symmetric diarylethynes were generated from the corresponding arylboronic acids/esters in satisfactory yield by using a palladium catalyst. The advantages of this protocol include the use of a readily available and easy‐to‐handle acetylene source, and a simple work‐up procedure. Abstract : Diarylethynes were efficiently synthesized by commercially available, inexpensive, and easy‐to‐handle calcium carbide with various arylboronic acids/esters. This method avoids the use of flammable and explosive acetylene gas.